Phylogeography of Loxodontomys micropus with comments on the alpha taxonomy of Loxodontomys (Cricetidae: Sigmodontinae) - Cañón Valenzuela, Carola Patricia (2010)
Loxodontomys micropus is a rodent that is widely distributed in Andean and Patagonian Argentina and Chile. This range covers a heterogeneous area that has been influenced by geologic and palaeoclimatic events, such as the glaciations during the Neogene. To investigate the genetic structure, phylogeographic pattern, and biogeographic history of this sigmodontine rodent we analyzed a 801-base-pair fragment of the mitochondrial genome (cytochrome-b gene) of 87 specimens from 24 localities from Argentina and Chile. Results indicate that L. micropus has a shallow genealogy that is geographically structured and is a taxon characterized by an historical population expansion. We discuss the distribution of the genetic variation of L. micropus in relation to population history and the concordance with other codistributed sigmodontine rodents. On the basis of molecular evidence, we suggest that the L. pikumche, corresponding to the second extant species of the genus, could be a junior synonym of L. micropus